The surface energetics of low dimensional nanomaterials - Ferguson, Auren (Trinity College (Dublin, Ireland). School of Physics, 2017)
Over the past two decades, there has been great interest in the discovery and research of low dimensional nanomaterials. These materials, such as carbon nanotubes and graphene, are amongst the strongest and most conductive materials ever discovered and show great promise for applications such as, electronics, renewable energy and polymer composites. Great strides in their understanding have been achieved, however, one material property that isn't well understood is their surface energy. Surface energy is a measure of the energy required to produce a unit area of surface and it controls how a material interacts with its environment. Therefore, understanding the surface energetics of low dimensional materials is very important, particularly in the case of the exfoliation of layered 2D materials in liquid, e.g. the exfoliation of graphite to produce graphene. This thesis develops a framework for the measurement and analysis of the surface energy of layered materials, revealing information such as the material's intrinsic surface energy and information about the type and amount of defects found on a sample surface. The surface energy of commercial graphites were measured using coverage dependent inverse gas chromatography (IGC), as it allows the mapping of the surface energy of materials as a function of surface coverage, called surface energy profiles. This method allows the examination of both high and low energy sites on a surface. At low coverage, high surface energy is measured, which reduces with increasing surface coverage and eventually plateaus, where surface energy becomes coverage independent. These profiles were empirically fitted to a stretched/compressed exponential function, allowing the extraction of the zero-coverage surface energy, the full coverage surface energy and the decay constant. Computer simulation showed that there are three types of graphite surface sites: the graphite basal plane, basal plane defects and edge defects … Over the past two decades, there has been great interest in the discovery and research of low dimensional nanomaterials. These materials, such as carbon nanotubes and graphene, are amongst the strongest and most conductive materials ever discovered and show great promise for applications such as, electronics, renewable energy and polymer composites. Great strides in their understanding have been achieved, however, one material property that isn't well understood is their surface energy. Surface energy is a measure of the energy required to produce a unit area of surface and it controls how a material interacts with its environment. Therefore, understanding the surface energetics of low dimensional materials is very important, particularly in the case of the exfoliation of layered 2D materials in liquid, e.g. the exfoliation of graphite to produce graphene. This thesis develops a framework for the measurement and analysis of the surface energy of layered materials, revealing information such as the material's intrinsic surface energy and information about the type and amount of defects found on a sample surface. The surface energy of commercial graphites were measured using coverage dependent inverse gas chromatography (IGC), as it allows the mapping of the surface energy of materials as a function of surface coverage, called surface energy profiles. This method allows the examination of both high and low energy sites on a surface. At low coverage, high surface energy is measured, which reduces with increasing surface coverage and eventually plateaus, where surface energy becomes coverage independent. These profiles were empirically fitted to a stretched/compressed exponential function, allowing the extraction of the zero-coverage surface energy, the full coverage surface energy and the decay constant. Computer simulation showed that there are three types of graphite surface sites: the graphite basal plane, basal plane defects and edge defects …
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin